The spatial and gendered politics of displaying family: exploring material cultures in grandfathers' homes. Issue 7 (2nd July 2016) - Tarrant, Anna
Abstract: This article analyses the meaning that 27 men who are grandfathers ascribed to the domestic material cultures of their homes, during an exploratory study that investigated their contemporary social and cultural geographies. In recounting stories about a number of items and artefacts placed about their homes during the interviews, that they specifically related to their experiences as grandfathers, the men provided insight into the various ways in which ageing men position themselves in ambivalent ways in relation to cultural stereotypes about grandparenthood, masculinities and ageing. Moving beyond the surface of the objects on display, their discussions also revealed the complex ways in which the material cultures of their homespaces are shaped by, and reproduce, diverse family relationships and their associated politics. The article contributes to, and bridges agendas in social and cultural geography that examine the relationship between the shifting meanings of home for older men, the politics of attending to the material and both the family and older masculine identities as spatial projects.